(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Childhood obesity is a key public health issue around the globe in developed and developing countries (Dugan, 2008). The recent worldwide increase in the prevalence of childhood obesity may be due in part to a decrease in children’s physical activity levels (Ball et al., 2001). It is necessary to develop early interventions to improve physical fitness in children and to prevent the increase of childhood obesity (Brunet et al., 2006). So, the aim of this study was to evaluate the body composition and physical fitness of children aged 5—7 years and to estimate the interaction between body composition components and physical fitness tests. Participants: 216 children participated in this study: 104 girls, mean age 5.90 ± 0.63 years and 112 boys — mean age 5.98 ± 0.50 years from Kaunas city (Lithuania) preschools. Methods: all the subjects have been measured for their height, body mass, waist circumference (WC) and skinfolds at 2 different places — triceps and subscapular. Body mass index (BMI) and percentage body fat mass (BFM) were evaluated. All the participants did four physical fitness tests including speed shuttle run, 20 meters distance run, standing long jump and throwing 1 kg ball. General physical fitness level was evaluated based on B. Sekita (1988) methods. Results. Results showed that BMI did not significantly differ between boys and girls, and was evaluated as “optimal” for both groups. BFM was significantly higher in girls (p < 0.001), and WC did not differ between genders. But WC had a tendency to increase with age in both boys and girls. Strong relationship was observed between BMI and BFM (r = 0.660, r = 0.660 respectively; p < 0.01), and between BMI and WC (r = 0.703, r = 0.826 respectively; p < 0.01) for both boys and girls. The results of physical tests showed that boys did all the tests better than girls (p < 0.01). When we evaluated the general physical fitness of each child, the results indicated that their physical fitness waslow, evaluated as “good enough” for most boys and girls. General physical fitness of children negatively but slightly correlated with BFM (r = –0.201; p < 0.001), it indicated that higher BFM determined lower evaluation of general physical fitness.Conclusions. Optimal body weight, according to body mass index, percentage body fat mass and waist circumference, was established for the bigger part of children, aged 5—7 years old. This study shows that physical fitness of children was low — evaluated as “good enough” and negatively correlated with body fat mass, showing that high body fat mass negatively impacted physical fitness. Key words: body mass index, percentage body fat mass, waist circumference, physical fitness.